2021
DOI: 10.1007/s10502-021-09381-0
|View full text |Cite
|
Sign up to set email alerts
|

Archives, linked data and the digital humanities: increasing access to digitised and born-digital archives via the semantic web

Abstract: Mass digitisation and the exponential growth of born-digital archives over the past two decades have resulted in an enormous volume of archives and archival data being available digitally. This has produced a valuable but under-utilised source of large-scale digital data ripe for interrogation by scholars and practitioners in the Digital Humanities. However, current digitisation approaches fall short of the requirements of digital humanists for structured, integrated, interoperable, and interrogable data. Link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…A survey from Hawkins (2022), indicated that the utilization of Linked Data is a promising approach to enhancing the accessibility of digitized and born-digital archives, resulting in the creation of enriched, interoperable, and integrated large-scale archival datasets that can be utilized in various ways (Hawkins, 2022). Presently, the primary focus of Archival Linked Data endeavours is the publication of archival metadata as Linked Data.…”
Section: Linked Data (Ld)mentioning
confidence: 99%
“…A survey from Hawkins (2022), indicated that the utilization of Linked Data is a promising approach to enhancing the accessibility of digitized and born-digital archives, resulting in the creation of enriched, interoperable, and integrated large-scale archival datasets that can be utilized in various ways (Hawkins, 2022). Presently, the primary focus of Archival Linked Data endeavours is the publication of archival metadata as Linked Data.…”
Section: Linked Data (Ld)mentioning
confidence: 99%
“…URI-based serendipitous discovery. Link-in and link-out linkages to the same URI can be aggregated as a networked relationship for information serendipity (Gracy, 2015;Hawkins, 2021;Hyvönen, 2012;Lemmens, 2020;Niu, 2016) to facilitate the discovery of useful or interesting information by chance or accident (Agarwal, 2015;Erdelez, 1999). By "following one's nose", link-in and link-out linkages can be regarded as semantic pathways to facilitate toURIsm (Baker et al, 2011)-based information navigation across various LD sources.…”
Section: Query and Browsementioning
confidence: 99%
“…As linkages are given semantic relationships explicitly, users' query and navigation can be expanded to encounter relevant information that exceeds expectations, such as related corporate bodies, persons families (CPFs), events, temporal and spatial contexts. Furthermore, link-in and link-out linkages also assemble various perspective meanings to build up contextual knowledge clues for interpretation (Ali and Warraich, 2018;Cole et al, An investigation of linked data catalogues 2013; Gracy, 2015;Hawkins, 2021;Klic et al, 2018). Therefore, semantic serendipitous discovery can be achieved through toURIsm-based connections and their assemblage from diverse heterogeneous LD sources.…”
Section: Query and Browsementioning
confidence: 99%
See 1 more Smart Citation
“…However, the content of digital and digitized records opens up the greatest potential for researchers. This becomes necessary attributes of the activities of archival services to collect data about their collections (Hawkins 2022).…”
Section: Public Access To Archival Materials In the Digital Agementioning
confidence: 99%